Application of electrophoretic deposition in capturing heavy metals from industrial wastewater to enhance health and environment aspects / Hartini Mahmood - Hartini, Mahmood (2018)
The industrial wastewater pollution is recognized to have a major negative impact on health and environment aspects. It’s mainly contributed by the generation of heavy metals which release to the water body after or during the manufacturing process. In terms of human health, the pollution from heavy metals will lead to serious diseases, while for the environment, the water crises and disturbance of aquatic life are the sequence from the heavy metals pollution. There are various types of water treatments availableto remove heavy metals such as chemical precipitation, ion exchange and membrane filtration. However, these treatments have limitations and weaknesses such as sludge generation, low selectivity, costly and some of them needadditional treatment to improve the removal efficiency.The electrophoretic deposition (EPD) is found to be one of the potential techniques that can be used to minimize these issues.EPD is the process of colloidal particles and regularly carried out in two electrode cells that dispersed in suspension medium with the existence of electric field. To obtain the optimum condition of EPD; the pH, current, particle size of heavy metals, type of electrode, and voltage are determined key factors.This study is to review the EPD process through several points of view, including the process principle, mechanism, effect of parameters and the exploration on EPD studies. A systematic review was used to answer a defined research question by collecting and summarizing all empirical evidence that fits pre-specified eligibility criteria.Additionally, several outlooks based on studies in the literature regarding to health and environmental effects from heavy metals are also presented in this paper.